The ills of extractivism: power and ecocriticism in Gabriel García Márquez - Ferreira, Felipe França (2024)
This article aims to point out and then analyze literary fragments of works by the colombian Gabriel García Márquez in the light of ecocriticism, which is one of the main contemporary developments of comparative literature and defined as a denunciation of how in general it is capitalism, with its extractivism, is the order that affects different ecosystems and produces injustices and collapses. Ecocriticism is linked to an ecological concern that dates back to the Enlightenment and in Brazilian literary criticism it begins to take its first steps. In Latin American literature, there are countless examples that contribute to the debate about environmental collapses caused by capitalism, and García Márquez's literature is part of this vast ecocritical group. To demonstrate the relationship between Gabriel García Márquez and ecocriticism, excerpts from his works that are consistent with this perspective will be exposed. In many of the works of the 1982 Nobel Prize-winning Colombian author, it is possible to observe criticism of criminal extractivism in Colombia, committed mainly by foreign agents, often in partnership with elites and local military governments. Thus, García Márquez is one of the authors who offers the most resources for ecocritical studies and paths to protecting ecosystems.